Chapter 10 Når dommeren i fotball dømmer feil ... - Johansen, Bjørn Tore (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"The aim of this study was to investigate characteristics of situations when top referees in soccer make an incorrect decision. Two expert panels, consisting of four top referees and four top players respectively, assessed 98 potential penalty shootout situations in Tippeligaen (Norwegian Premier League). The situations in which all the expert panels considered that the match referee made an incorrect decision (N = 14) were then analyzed based on recommended technical refereeing criteria and guidelines, as the referee's distance to, angle to and insight into these penalty situations. The results revealed that in 11 of these 14 situations the referee had a greater distance than recommended. Furthermore, both the angle and insight were only of medium or poor nature. This may indicate that the referee had limited basis when assessing these situations, and subsequently landed on a wrong decision. Findings also showed that referees were more likely to go in favor of high status teams. This will be a topic for discussion in this article, based on the theory of dealing with mistakes and social pressure."